The Determinant Factors of Earnings Persistence - Mia Oktavia; Yulius Kurnia Susanto (Gorontalo State University, 2022)
The purpose of this research is to provide empirical evidence about the effect of operating cash flow, sales volatility, cash flow volatility, operating cycle, and book tax difference on earnings persistence. The company used in this research is manufacturing company listed in Indonesia Stock Exchange (IDX) from 2016 until 2020. Samples of this research were selected based on the purposive sampling method and resulted in 43 companies, therefore the data used for this research amounting to 215 data. The data obtained from these samples were analyzed using multiple regression method. The result of this research show that operating cycle have influence on earnings persistence. While operating cash flow, sales volatility, cash flow volatility, and book tax difference have no influence on earnings persistence.